2022
DOI: 10.1177/01926233221090518
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity and Local Tolerance of a Novel Spike Protein RBD Vaccine Against SARS-CoV-2, Produced Using the C1 Thermothelomyces Heterothallica Protein Expression Platform

Abstract: Coronavirus disease 2019 (COVID-19) has caused the ongoing COVID-19 pandemic and there is a growing demand for safe and effective vaccines. The thermophilic Thermothelomyces heterothallica filamentous fungal host, C1-cell, can be utilized as an expression platform for the rapid production of large quantities of antigens for developing vaccines. The aim of this study was to evaluate the local tolerance and the systemic toxicity of a C1-cell expressed receptor-binding domain (C1-RBD) vaccine, following repeated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…These studies have used different subunits, such as the hemagglutinin for In uenza A virus, the RBD for SARS-CoV-2 and part of the Gc glycoprotein for Schmallenberg virus 18,19,23 . A previous study testing C1-derived SARS-CoV-2 RBD protein in rabbits for toxicology did not show any local or systemic side effects of fungal produced proteins, indicating its potential safety for use in humans 24 .…”
Section: Discussionmentioning
confidence: 79%
“…These studies have used different subunits, such as the hemagglutinin for In uenza A virus, the RBD for SARS-CoV-2 and part of the Gc glycoprotein for Schmallenberg virus 18,19,23 . A previous study testing C1-derived SARS-CoV-2 RBD protein in rabbits for toxicology did not show any local or systemic side effects of fungal produced proteins, indicating its potential safety for use in humans 24 .…”
Section: Discussionmentioning
confidence: 79%
“…Moreover, in the study done by Ramot et. al., it was shown that in New Zealand rabbits, the SARS-CoV-2-RBD produced with the C1 system, did not induced any adverse effects or systemic toxicity and induced the production IgG antibodies against SARS-CoV-2 36 . Furthermore, Lazo and colleagues, proved that immunization with SARS-CoV-2-RBD produced in the C1 system, induced a similar humoral response in mice as recombinant SARS-CoV-2-RBD produced in HEK293 cells 17 .…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the observed findings are immunostimulatory effects, which, together with their reversible nature, can be considered non-adverse. Inflammatory reactions at the injection site are considered as intended reactions representing the immune response to the antigen ( Ramot et al, 2022 ). This has been described earlier in a workshop report ( Van Der Laan et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%